2018
DOI: 10.1016/j.ijhydene.2018.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Production and stability of low amount fraction of formaldehyde in hydrogen gas standards

Abstract: Formaldehyde is an intermediate of the steam methane reforming process for hydrogen production. According to International Standard ISO 14687-2 the amount fraction level of formaldehyde present in hydrogen supplied to fuel cell electric vehicles (FCEV) must not exceed 10 nmol mol-1. The development of formaldehyde standards in hydrogen is crucial to validate the analytical results and ensure measurement reliability for the FCEV industry. NPL demonstrated that these standards can be gravimetrically prepared and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The stability of the HCOOH in hydrogen was studied with FTIR by NPL and with PD-HID and electrophoresis by VTT before and after fuel cell measurements. The stability of HCHO in H 2 at NPL has been reported by Bacquart et al 38 The online gas sampling was conducted with a gas chromatograph for CO, CO 2 and CH 4 during all measurements. The gas chromatograph was equipped with a packed Carboxen-1000 column (45/60 mesh, 2 m × 1/8") and a FID with a methanizer built in-house.…”
Section: Methodsmentioning
confidence: 95%
“…The stability of the HCOOH in hydrogen was studied with FTIR by NPL and with PD-HID and electrophoresis by VTT before and after fuel cell measurements. The stability of HCHO in H 2 at NPL has been reported by Bacquart et al 38 The online gas sampling was conducted with a gas chromatograph for CO, CO 2 and CH 4 during all measurements. The gas chromatograph was equipped with a packed Carboxen-1000 column (45/60 mesh, 2 m × 1/8") and a FID with a methanizer built in-house.…”
Section: Methodsmentioning
confidence: 95%
“…A previous study [28] has showed how formaldehyde is unstable in a hydrogen matrix, so reaction (1) could potentially represent the first step of the degradation of formic acid into secondary products once formaldehyde is formed, as indicated by Equation (4):…”
Section: Thermodynamic Calculationsmentioning
confidence: 99%
“…Requirements for grade D hydrogen in ISO 14687 [21] include specifications for maximum levels of carbon dioxide, nitrogen, argon, sulfurcontaining species (see section 8.2), halides (see sections 8.8 and 8.10), carbon monoxide (see section 8.4), formic acid (see section 8.12) and formaldehyde (see section 8.11). An assessment of the likelihood of finding these impurities has been made in hydrogen from various sources [57]. Also a review of available methods for hydrogen purity assessments has been made [58].…”
Section: Hydrogenmentioning
confidence: 99%
“…The sensitivity of the CRDS method fulfils therefore criteria set in [21] and [133]. Static formaldehyde in hydrogen gas standards are highly unstable due to degradation of formaldehyde into methanol and dimethoxymethane [57]. Dynamic preparation of formaldehyde standards is therefore the method of choice to prepare calibration gas mixtures of formaldehyde in hydrogen.…”
Section: Formaldehydementioning
confidence: 99%